2021
DOI: 10.1155/2021/5516285
|View full text |Cite
|
Sign up to set email alerts
|

Plant Natural Compounds in the Treatment of Adrenocortical Tumors

Abstract: Plant natural products are a plethora of diverse and complex molecules produced by the plant secondary metabolism. Among these, many can reserve beneficial or curative properties when employed to treat human diseases. Even in cancer, they can be successfully used and indeed numerous phytochemicals exert antineoplastic activity. The most common molecules derived from plants and used in the fight against cancer are polyphenols, i.e., quercetin, genistein, resveratrol, curcumin, etc. Despite valuable data especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 161 publications
(212 reference statements)
0
2
0
Order By: Relevance
“…Quercetin has many biological properties and generally long‐standing anti‐inflammatory capacities. It was also reported that quercetin showed neurological, antiviral, anti‐allergic, and antiangiogenesis effects 95,97 . Furthermore, research indicated that it has significant anticancer potential.…”
Section: Advancements In Natural Substance Enhancement Through Nanote...mentioning
confidence: 98%
See 1 more Smart Citation
“…Quercetin has many biological properties and generally long‐standing anti‐inflammatory capacities. It was also reported that quercetin showed neurological, antiviral, anti‐allergic, and antiangiogenesis effects 95,97 . Furthermore, research indicated that it has significant anticancer potential.…”
Section: Advancements In Natural Substance Enhancement Through Nanote...mentioning
confidence: 98%
“…It was also reported that quercetin showed neurological, antiviral, anti-allergic, and antiangiogenesis effects. 95,97 Furthermore, research indicated that it has significant anticancer potential. The anticancer activity of quercetin is considered against various types of malignancy involving breast, colorectal, liver, lung, prostate, and skin cancer.…”
Section: Quercetinmentioning
confidence: 99%